(untitled) (Baghdad Science Journal, 2022)
Rheumatoid arthritis (RA), is an autoimmune, and inflammatory disease that is closely related to the destruction of cartilage and bone. DC-SIGN are important types of C-type lectin receptors (CLRs), expressed on dendritic cells and macrophages, and have a central role in regulating innate and adaptive immunity, function as pattern recognition receptors, and as cell adhesion molecules. Recent evidence has demonstrated that DC-SIGN is involved in the pathophysiological of chronic inflammation, so DC-SIGN has been linked to several autoimmune and may play an essential indicator in the pathogenesis and progression of RA. Therefore, the purpose of this study is to determine the serum level of DC-SIGN in RA patients, as well as the level of DC-SIGN based on demographic characteristics. Fifty Iraqi RA patients were enrolled in the study, and a control sample of 38 healthy individuals (ascertain by laboratory and clinical tests) were included and matched by gender, age, and ethnicity with the patients. The DC-SIGN concentration was calculated in the patients’ serum and compared to control using the ELISA assay and the results revealed significantly increased serum level of DC-SIGN (12.047 ± 1.114 vs. 6.863 ± 0.806 ng/ml) was recorded in RA patients compared to controls. When correlating results, it was shown that the concentration of DC-SIGN in the serum did not record a significant difference between gender and age, as well as the blood groups. To determine the impact of the therapeutic status in RA patients on the DC-SIGN level, it was found that the concentration of DC-SIGN level was higher in untreated patients compared to treated patients. Regarding viral infection, when an investigation was conducted in RA patients infected with SARS-CoV-2, the serum level of DC-SIGN in RA patients with COVID-19 showed no change in concentrations compared to uninfected RA patients.